Gas Chromatography Analysis of Artificially Inoculated Agarwood Compounds Related to High Quality Agarwood from Malaysia Plantation - Sufihana, Yusof; Saiful Nizam, Tajuddin; Rofiza, Mansor; Pang, Wei Cheng; Aizi Nor Mazila, Ramli (ISSR Publishing, 2018)
The aim of this study is to determine the quality of artificially inoculated agarwood from Aquilaria malaccensis trees obtained from a plantation in East Malaysia using gas chromatography (GC). The agarwood quality was measured by existence and amount of aromatic and terpene compounds especially those which were recorded in high-quality agarwood such as α-guaiene, β-selinene, aromadendrene and agarospirol. For quality determination purpose of artificially inoculated agarwood, samples were collected from selected plantation area. Solid Phase Micro Extraction (SPME) method was performed to collect the volatile compounds released by wood sample. There were five commercial inoculants (Ino A, B, C, D and E) that had been used for inoculation of A. malaccensis in agarwood plantation. GC analysis revealed the presence of important compounds related to high-quality agarwood such as 4-phenyl-2-butanone, β-selinene, α-bulnesene, and agarospirol in agarwood sample produced from artificial inoculation using Ino A inoculant. Most of these compounds were mostly absent in the agarwood samples that have been inoculated with other inoculants (Ino B, C, D and E). Several important compounds related to high-quality agarwood were detected. The results obtained in this research clearly indicated a promising potential of artificially inoculated agarwood as an alternative source of high-quality agarwood.